1988
DOI: 10.1128/jcm.26.8.1592-1594.1988
|View full text |Cite
|
Sign up to set email alerts
|

Cellular fatty acid composition of Kingella species, Cardiobacterium hominis, and Eikenella corrodens

Abstract: We determined the cellular fatty acid composition of reference strains and clinical isolates of each of the three Kingella species, Cardiobacterium hominis, and Eikenella corrodens by using capillary gas chromatography. Kingella denitrificans and Kingella kingae contained myristic (14:0) and palmitic (16:0) acids as major acids, whereas cis-vaccenic (18:1 w7c) and palmitic acids were the major acids in Kingella indologenes, C. hominis, and E. corrodens. C. hominis differed from the other four species by the ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
7
0

Year Published

1989
1989
2016
2016

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 6 publications
(13 reference statements)
0
7
0
Order By: Relevance
“…In previous studies, we have found that cellular fatty acid analysis of bacterial cells provides useful information for their identification and classification (7,(10)(11)(12). In this report, we describe the cellular fatty acid composition of CDC group DF-3 strains and their biochemical and chemical relationships to other bacteria which contain similar branched-chain fatty acids.…”
mentioning
confidence: 87%
“…In previous studies, we have found that cellular fatty acid analysis of bacterial cells provides useful information for their identification and classification (7,(10)(11)(12). In this report, we describe the cellular fatty acid composition of CDC group DF-3 strains and their biochemical and chemical relationships to other bacteria which contain similar branched-chain fatty acids.…”
mentioning
confidence: 87%
“…and Cardiobacterium hominis, with which it shares certain phenotypic characteristics, are distinguishable by CFAs (157). Eikenella corrodens contains less C14:0 than the other two and has C18:1.,7c and C16:0 as the major CFAs and C16:1, C12:0, C14:0, and C18:0 in smaller amounts (125,157). Cardiobactenium, hominis is the only one of the three characterized by the absence of 3-OH-C12:0.…”
Section: Identification To Genus or Speciesmentioning
confidence: 99%
“…The cells from one plate were harvested and saponified, and the liberated fatty acids were methylated as previously described (13). The resulting fatty acid methyl esters were analyzed by gas-liquid chromatography (GLC) with the HP5898A Microbial Identification System (Hewlett-Packard Co., Avondale, Pa.) described in an earlier report (17). Tentative identifications of the fatty acid methyl esters were confirmed by computer-calculated equivalent carbon-chain-length values, hydrogenation, acetylation, and combined GLC-mass spectrometry.…”
mentioning
confidence: 99%